ANALISIS RESTRUKTURISASI PEMBIAYAAN PERBANKAN SYARIAH DIMASA COVID-19 TAHUN 2020 - Dody Wijaya Hardi; Muhammad Ilham (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
The COVID-19 outbreak that originated in Wuhan has been declared a pandemic, not only affecting the health sector but also affecting other sectors that affect it. One of them is in the banking business, as a result, many customers feel that their business is not running smoothly. The result is congestion in banking activities. Thus, the government has provided a stimulus to customers through the POJK to provide relief in the financing, including sharia banking financing. This research is of course included in the normative juridical research method with qualitative research types, as the main ingredient, of course, referring to POJK Number 11/POJK.03/2020 concerning National Economic Stimulus. Then added with secondary materials in the form of the Civil Code and PERMA. steps and strategies to save financing as an effort by sharia banks to improve the financing position and financial condition of customers by re-positioning the financing through contract renegotiation and refinancing in financing contracts